Gastric Mucosa-Associated Microbial Signatures of Early Gastric Cancer - Wang, Lili; Xin, Yongning; Zhou, Jianhua; Tian, Zibin; Liu, Chenguang; Yu, Xinjuan; Meng, Xinying; Jiang, Weina; Zhao, Shoufeng; Dong, Quanjiang (Frontiers in Microbiology, 2020)
Alterations in the microbiome are associated with the development of gastric cancer. Our study aimed to identify dysbiotic features in early gastric cancer. The gastric microbiome was assessed in early gastric cancer (n = 30), advanced gastric cancer (n = 30) and chronic gastritis (n = 60). The results demonstrated significant differences in the microbial profile and composition between early and advanced gastric cancer, suggesting alterations associated with gastric cancer progression. Linear discriminant analysis effect size (LEfSe) analyses identified 32 bacterial genera that were associated with early gastric cancer. Functional analyses of the gastric microbiome showed that the production of urease and synthesis of bacterial flagella were weakened in early gastric cancer, while the glycolysis of fructose and hydrolysis of glycosides were enhanced. A classifier based on a random forest machine learning algorithm identified a microbial signature that distinguished early gastric cancer from chronic gastritis or advanced gastric cancer with high accuracy. The correct identification of the signature was further validated in independent cohorts. This signature enriched of bacteria with varied abundance, high degree of bacterial interactions and carcinogenic potentials. Constrained principal coordinate analyses revealed that the presence of Helicobacter pylori and the cagA and vacA virulence genotypes influenced the structure of the gastric microbiome. To determine the impacts of host genetic variations on the gastric microbiome, six previously reported single nucleotide polymorphisms (SNPs) were examined. The minor allele of MUC1 rs4072037 was associated with an increased abundance of Ochrobactrum. The gastric microbiome altered in early gastric cancer, which might be attributed in part to host genetic variations, H. pylori infection, bacterial virulence and environmental adaptations. The identified microbial signature could serve as biomarkers for clinical assessment of gastric cancer risk in high-risk patients.